Implications of household-level evidence for policy models: the case of macro-financial linkages - Muellbauer, J (University of Oxford, 2020)
Macroeconomic policy models should track the different channels of monetary transmission, providing a framework for Monetary Policy Committees. They should also be useful for assessing risks to financial stability, including for designing macroprudential stress tests and instrument settings in the new macroprudential toolkits. Current policy models, including the 'semi-structural' non-DSGE econometric models such as FRB-US, are seriously deficient in these respects, failing to capture the credit channel and the role of real estate in the financial accelerator that operated in the global financial crisis, and in key transmission channels in the recovery. Furthermore, developments in economic theory, greatly encouraged by new evidence, have rendered redundant the previously accepted micro-foundations for household behaviour in these policy models. A multi-purpose policy model needs to include a household-housing sub-system. This should contain a consumption function broadly consistent with the micro-evidence with equations for permanent income, for the balance sheet drivers, and for residential investment. To capture the credit channel, this block of the model needs to embed common credit conditions in the equations. Sub-system estimation is required to impose the cross-equation restrictions implied by these common factors.